2017
DOI: 10.1590/s1980-220x2016048003253
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in pregnancy: prevalence and associated factors

Abstract: Objective: Evaluating the occurrence of anxiety in pregnant women and the factors associated with its occurrence; comparing the presence of anxiety in each gestational trimester. Method: A descriptive, correlational cross-sectional study. Data were collected from January to May 2013 using the Hospital Anxiety Subscale and a form composed of socioeconomic characterization; gestational anamnesis; life-changing habits and events; preexisting conditions and interpersonal relationships. Results: A total of 209 preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
47

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(149 citation statements)
references
References 21 publications
5
65
0
47
Order By: Relevance
“…The results of this study indicate that most pregnant women do not experience anxiety during pregnancy. This is in line with research conducted by Silva et al [15], which shows that most pregnant women do not experience anxiety. Mothers who have multiple pregnancy experience tend to get less anxiety during the pregnancy process.…”
Section: B Anxiety Low Back Pain (Lbp) and Sleepsupporting
confidence: 93%
“…The results of this study indicate that most pregnant women do not experience anxiety during pregnancy. This is in line with research conducted by Silva et al [15], which shows that most pregnant women do not experience anxiety. Mothers who have multiple pregnancy experience tend to get less anxiety during the pregnancy process.…”
Section: B Anxiety Low Back Pain (Lbp) and Sleepsupporting
confidence: 93%
“…Chan et al [18] found similar results in China in 2013 (52.4%). Silva et al [19], also got the same results (41.1%) in Brazil, in 2017. Whereas Giardinelli et al [16] reported almost the same frequencies of both secondary (47%) and high level (46.4%) in Italy in 2012.…”
Section: Deficit In Education and Economic Resourcessupporting
confidence: 54%
“…Various studies of mental disorders during pregnancy have reported a different prevalence of depression, anxiety and other mental disorders (Rubertsson et al, 2014;Kang et al, 2016;Faisal-Cury and Menezes, 2007;Madhavanprabhakaran et al, 2015;Silva et al, 2017). Some studies reported the prevalence of mental disorders 17% in the first trimester of pregnancy and 13% in the third trimester and the prevalence of depression and anxiety 13.5-42% during pregnancy by the General Health Questionnaire (GHQ) (Evans et al, 2001;Villanueva et al, 2000).…”
Section: Introductionmentioning
confidence: 99%